Highly stretchable, high efficiency room temperature self-healing polyurethane adhesive based on hydrogen bonds – applicable to solid rocket propellants. Issue 31 (22nd July 2021) - Jing, Tu; Heng, Xu; Guifeng, Xiang; Ling, Chen; Pingyun, Li; Xiaode, Guo
Abstract : The introduction of weak hydrogen bonds based on the isophorone structure enables the polymer to have high stretchability and self-healing ability at room temperature to heal propellant damage. Abstract : The formation and expansion of cracks in a propellant would induce debonding at the interface between different constituents and may even cause explosion of the propellant during launch. One way to prohibit debonding is the employment of self-healing polyurethane adhesives, which can heal cracks in the early stage. In this work, polypropylene glycol and isophorone diamine were used to prepare polyurethane adhesive with high-efficiency self-healing ability. The differences between the mechanical and self-healing properties of polyurethanes with a hard segment structure composed of different isocyanates were studied. The experimental results showed that PPG-IP-PA (polyurethane synthesized using polypropylene glycol, isophorone isocyanate and isophorone diamine) has excellent mechanical properties and high-efficiency room temperature self-healing ability. When compared with other polyurethanes, PPG-IP-PA has a strong molecular chain motion ability, and its continuous ring hard segment structure ensures the overall mechanical properties. Its maximum tensile strength can be up to 3.85 MPa and elongation at break almost reached 3000%. After placing at room temperature for 12 h, the mechanical properties of PPG-IP-PA can be fully restored. When PPG-IP-PA was applied to a propellant, it can restore 70% of the tensile strength of the completely broken grain after being placed at room temperature for 12 h, and there was no obvious interference to the thermal decomposition of AP-Al components. Our results provide a new designing concept in dealing with the debonding of components in propellants.